The Influence of Cash Flow, Profitability, and Sales Growth on Stock Prices With Capital Structure as Intervening Variables in Banking Companies Listed on the Indonesia Stock Exchange 2015-2019 - Nasution, Monica Angelin; Putri, Tengku Mella Syafrian; Sani, Ahmad; Syamsul Bahri, Syamsul Bahri (Cattleya Darmaya Fortuna, 2023)
This study aims to determine the effect of cash flow, profitability and sales growth on share prices and analyze the effect of cash flow, profitability and sales growth on stock prices with a capital structure as a variable in banking companies listed on the Indonesia stock exchange for the 2015–2019 period. Sampling using purposive sampling so that the number of samples taken is 34 companies with 5 years of observation with a total sample of 170 samples. This study uses secondary data, data collection techniques using documentation studies and literature studies and the method used is path testing. The results of this study indicate that profitability has a significant effect on capital structure, while cash flow and sales growth have no significant effect on capital structure in banking companies listed on the IDX for the 2015–2019 period. Cash flow, sales growth and capital structure have a significant effect on stock prices, while profitability has no significant effect on stock prices in banking companies listed on the IDX for the 2015–2019 period. The capital structure can mediate the effect of cash flow, profitability and sales growth on stock prices in banking companies listed on the IDX for the 2015–2019 period.